KIR- Ligand Interactions in Hypertensive Disorders in Pregnancy - Stefańska, Katarzyna; Tomaszewicz, Martyna; Dębska-Zielkowska, Joanna; Zamkowska, Dorota; Piekarska, Karolina; Sakowska, Justyna; Studziński, Maciej; Tymoniuk, Bogusław; Adamski, Przemysław; Jassem-Bobowicz, Joanna; Wydra, Piotr; Leszczyńska, Katarzyna; et al. (Frontiers in Immunology, 2022)
Hypothesis The activity of natural killer (NK) cells is considered an important factor for the tolerance of the fetus during pregnancy. The complications of pregnancy, such as hypertensive disorders (HDP), may be therefore associated with this immune compartment. Methods The current study included 41 pregnant women diagnosed with HDPs (Gestational Hypertension; GH or Preeclampsia; PE) and 21 healthy women. All the patients were under continuous obstetric care during the pregnancy and labour. The number of mother-child mismatches within killer immunoglobulin-like receptors (KIRs), their ligands [MM], and missing KIR ligands [MSLs] was assessed. KIRs and their ligands were assessed with Next Generation Sequencing (NGS) and Polymerase Chain Reaction Sequence-Specific Oligonucleotide (PCR-SSO) typing. The subsets of NK cells were assessed with multicolor flow cytometry and correlated to the number of MSLs. Results The number of MSLs was significantly higher in HDP patients when compared to healthy non-complicated pregnancy patients. Some MSLs, such as those with 2DS2 activating KIR, were present only in HDP patients. The percentage of CD56+CD16-CD94+ NK cells and CD56+CD16-CD279+ NK cells correlated with the number of MSLs with inhibiting KIRs only in healthy patients. In HDP patients, there was a correlation between the percentage of CD56-CD16+CD69+ NK cells and the number of MSLs with inhibiting and activating KIRs. As compared to the healthy group, the percentage of CD56+CD16-CD279+ NK cells and CD56-CD16+CD279+ NK cells were lower in HDP patients. HDP patients were also characterized by a higher percentage of CD56+CD16+perforin+ NK cells than their healthy counterparts. Conclusions Patients with HDP were characterized by a higher number of MSLs within the KIRs receptors. It seemed that the number of MSLs in the healthy group was balanced by various receptors, such as CD94 or inhibitory CD279, expressed on NK cells. Conversely, in HDP patients the number of MSLs was associated with the activation detected as the increased level of CD69+ NK cells.